Peran Program Pemerintah dan Masyarakat dalam Pendidikan untuk Mewujudkan Kesejahteraan Anak - Septiani Nabila Putri; Risbon Sianturi; Sinta Indah Pratiwi; Tasya Nazwa Nafisa; Widia Andini (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study aims to analyze the role of government programs and community participation in education as an effort to promote children's well-being. The research uses a literature review approach by examining relevant scientific articles obtained from academic databases. The data were analyzed using a qualitative descriptive method through processes of organizing, comparing, and interpreting findings from various studies. The results show that government programs play an important role in improving access to and the quality of education through the provision of services and supportive policies for child development. In addition, community participation, especially from families and the surrounding social environment, contributes to creating a supportive and conducive learning atmosphere. The collaboration between government and community is a key factor in ensuring that educational efforts effectively support children's overall development and well-being. Therefore, strengthening cooperation among stakeholders is necessary to enhance the implementation of educational programs in a sustainable manner